2017
DOI: 10.1108/jcp-11-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences, paraphilias, and serious criminal violence among federal sex offenders

Abstract: Purpose Adverse childhood experiences (ACEs) are a broad conceptual framework in the social sciences that have only recently been studied within criminology. The purpose of this paper is to utilize this framework by applying it to one of the most potentially dangerous forensic populations. Design/methodology/approach Archival data from 225 federal sex offenders was used to perform descriptive, correlational, and negative binomial regression models. Findings There was substantial evidence of ACEs including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 79 publications
2
47
0
Order By: Relevance
“…Additional research is needed to examine how and to what degree adverse childhood experiences are associated with variance in specific forms of serious crime, including homicide and aggravated robbery. Moreover, while there is considerable evidence that sexual abuse victimization can be a distal predictor of subsequent sexual offending [17,18,19,20,21], much less is known about how poverty, physical abuse, emotional abuse, and other deprivations are linked to other forms of violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research is needed to examine how and to what degree adverse childhood experiences are associated with variance in specific forms of serious crime, including homicide and aggravated robbery. Moreover, while there is considerable evidence that sexual abuse victimization can be a distal predictor of subsequent sexual offending [17,18,19,20,21], much less is known about how poverty, physical abuse, emotional abuse, and other deprivations are linked to other forms of violence.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Boduszek and colleagues [15] found that male prisoners in Poland who had been exposed to family violence were approximately six times more likely to perpetrate a homicide than offenders who lacked violence exposure. In terms of sexual violence, a host of investigators have found that assorted adverse childhood experiences, particularly childhood sexual abuse victimization, were associated with an increased likelihood of perpetrating sexual crimes during adolescence or adulthood [16,17,18,19,20,21]. The evidence is clear that adverse childhood experiences increase the liability for externalizing symptoms and diverse forms of antisocial conduct.…”
Section: Introductionmentioning
confidence: 99%
“…H. Cohen & Spidell, 2016; T. H. Cohen & VanBenschoten, 2014; Drury et al, 2017; Walters & Cohen, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, in this case, behaviour moved back, forth and between categories, a regression and movement which is not presented as possible in that model either. It is pertinent to note that multiple sexual paraphilias are frequently found in the same individual (Marshall 2007), particularly when necrophilia is identified (Gayford 1997:312), and when, as in this case, a sexual offender has experienced an adverse childhood experience such as sexual abuse (Drury et al 2017). As such, those behaviours related to necrophilia in similarity could perhaps offer guidance to the construction of a necrophilia classification system in the future.…”
Section: Discussionmentioning
confidence: 95%